Cobalt–nickel sulfide nanosheets modified by nitrogen-doped porous reduced graphene oxide as high-conductivity cathode materials for supercapacitor. (1st December 2020) - Hong, Xianyong; Li, Jinghua; Zhu, Guisheng; Xu, Huarui; Zhang, Xiuyun; Zhao, Yunyun; Zhang, Jian; Yan, Dongliang; Yu, Aibing
Abstract: High conductivity NiCo2 S4 (NCS) nanosheets in situ grown in porous nitrogen-doped reduced graphene oxide (PN-rGO) materials were successfully prepared via a simple hydrothermal method. A synergistic effect between the NCS and PN-rGO matrix is observed on the electrochemical performance of the composites. PN-rGO/NCS exhibits an equivalent ultralow diffusion resistance and charge transfer resistance (0.16 Ω), ultrahigh specific capacitance (1, 687 F g −1 at a current density of 0.5 A g −1 ), and an excellent rate capability (1, 478 F g −1 at a current density of 10 A g −1 ). The asymmetric supercapacitor (ASC) is designed with PN-rGO/NCS as the positive electrode and active carbon as the negative electrode. The ASC device exhibits a high capacitance (355.5 F g −1 at a current density of 1 A g −1 ). Density functional theory calculations show PN-rGO/NCS to increase the electrical conductivity of the material, and concomitantly the electrochemical performance. The data suggest that the PN-rGO/NCS hybrid structure can be considered as a future supercapacitor electrode material. Graphical abstract: Image, graphical abstract